2017
DOI: 10.1021/acs.joc.7b02722
|View full text |Cite
|
Sign up to set email alerts
|

Straight Access to Indoles from Anilines and Ethylene Glycol by Heterogeneous Acceptorless Dehydrogenative Condensation

Abstract: The development of original strategies for the preparation of indole derivatives is a major goal in drug design. Herein, we report the first straight access to indoles from anilines and ethylene glycol by heterogeneous catalysis, based on an acceptorless dehydrogenative condensation, under noninert conditions. In order to achieve high selectivity, a combination of Pt/AlO and ZnO have been found to slowly dehydrogenate ethylene glycol generating, after condensation with the amine and tautomeric equilibrium, the… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
19
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 32 publications
(19 citation statements)
references
References 78 publications
0
19
0
Order By: Relevance
“…Then, in order to explain the effect of polar substituents on this reaction, [30] the control experiment of biguanide with different alcohols 2 aa and 2 ab was set up. After four hours, NMR analysis showed that the molar ratio of two products ( 18 aa vs 18 ab ) was 3.3 : 1, which disclosed that the reaction was more favorable for benzyl alcohol containing with an electron‐donating group.…”
Section: Resultsmentioning
confidence: 99%
“…Then, in order to explain the effect of polar substituents on this reaction, [30] the control experiment of biguanide with different alcohols 2 aa and 2 ab was set up. After four hours, NMR analysis showed that the molar ratio of two products ( 18 aa vs 18 ab ) was 3.3 : 1, which disclosed that the reaction was more favorable for benzyl alcohol containing with an electron‐donating group.…”
Section: Resultsmentioning
confidence: 99%
“…In 2018, Ballesteros-Garrido and co-workers described the synthesis of different indoles from anilines and ethylene glycol in the presence of Pt/Al 2 O 3 and ZnO at 175 8 8C (Scheme 5). [35] Interestingly,t he reaction does not proceed well in the absence of ZnO.Under optimized conditions,the condensation of various anilines with ethylene glycol afforded the corresponding indoles in moderate to good yields. However,o nly anilines with donor substituents can be converted to the corresponding indoles with good yields.…”
Section: Methodsmentioning
confidence: 99%
“…In 2018, Ballesteros‐Garrido and co‐workers described the synthesis of different indoles from anilines and ethylene glycol in the presence of Pt/Al 2 O 3 and ZnO at 175 °C (Scheme 5). [35] Interestingly, the reaction does not proceed well in the absence of ZnO. Under optimized conditions, the condensation of various anilines with ethylene glycol afforded the corresponding indoles in moderate to good yields.…”
Section: Noble Metal‐based Heterogeneous Catalystsmentioning
confidence: 99%
“…The Lewis acid–base nature of the support is also crucial for the success of numerous tandem or domino reactions. Metal oxides [32–38] and heteroatom‐doped carbons [25] as the supports usually have acid–base pair sites, which are sufficient to promote the dehydrogenation of alcohols and C–C/C–N coupling without the need for additional base in these transformations. Compared with basic or relatively acidic supports, amphoteric supports usually have higher catalytic activity, which can be attributed to the coexistence of acidic and basic sites on the support surface.…”
Section: General Considerationsmentioning
confidence: 99%